The Impact of Social and Cultural Factors on the Effectiveness of Tourism Management in Major Projects: A Human-Centered Perspective - Al-Jindi, Ashraf Fawzy (Journal of Humanities & Social Sciences, 2025)
This study highlights the impact of social and cultural factors on the effectiveness of managing major tourism projects, emphasizing the importance of adopting a human-centered approach that enhances the sustainability of these projects and their positive integration with the local community. The research employed a descriptive-analytical methodology, in addition to a case study of a major tourism project in the Kingdom of Saudi Arabia, aiming to analyze the interaction between socio-cultural factors and tourism management practices. Data were collected through a review of relevant literature, document analysis, and semi-structured interviews with various stakeholders. The findings reveal that social and cultural considerations play a pivotal role in the success of tourism projects, necessitating the integration of these aspects into planning and implementation phases to ensure the achievement of sustainable development goals. Objectives: The study aims to examine the effect of social and cultural factors on the management of major tourism projects, focusing on the challenges faced and proposing a human-centered framework that promotes positive interaction between these projects and the local community to ensure their effectiveness and sustainability. Methodology: The research adopts a descriptive-analytical approach supported by an applied case study. It utilizes semi-structured interviews with experts, surveys targeting local communities, and a review of previous literature in the fields of sustainable tourism and tourism management. Scope of the Study: The Kingdom of Saudi Arabia, with a focus on major projects in emerging tourist cities.  Findings: The results revealed a direct relationship between local community support and the success of tourism project management. They also uncovered influential cultural challenges and emphasized the importance of involving residents in the planning process. This contributed to the proposal of a flexible administrative model that considers human and cultural dimensions.